(untitled) (Journal of Hama University, 2024)
The present study aimed to identify the role of the school principal in the process of educational supervision in light of the principles of total quality, the study estimates differences between the managers for this role due to the variables (academic qualification, years of experience, training courses). Was the use of analytical and descriptive approach applied researcher to identify the sample consisting of (88) director of basic education (Episode I and II) in Lattakia was withdrawn using a simple random sample after the sample is determined using statistical law. The research found the following results: - The need to plan and act within the principles of total quality management through: - Encourage the effective leadership behavior among students, and provide them with educational experiences develop their personality in an integrated manner. - Provide an opportunity for creativity and innovation of teachers, and urged them to improve their classroom, commitment and teamwork, and follow up their performance in light of specific criteria and indicators. - Seeking to spread a culture change among staff and teachers, and help them develop a variety of methods of assessment. - The presence of statistically significant differences at the level of significance / 0.05 / between the mean estimates of directors for their role in the process of educational supervision due to the variable of academic qualification, these differences in favor of Qualification Diploma qualification. - The presence of statistically significant differences at the level of significance / 0.05 / between the mean estimates of directors for their role in the process of educational supervision due to the variable number of years of experience, and these differences for the benefit of years of experience (10-15) years, and more than 15 years, One of the most important proposals presented by the research was to provide a comprehensive quality management unit in the Ministry of Education and its affiliated directorates, provide supervision and follow-up, prepare cadres responsible for implementing comprehensive quality management programs and its principles, and hold training courses for principals, teachers, and school administration in general on comprehensive quality and its principles and disseminate its values and trends.